Rehabilitation of an edentulous mouth with severe mandibular ridge resorption using neutral zone impression technique: a case report (Bangladesh Journal of Medical Science, 2014)
Alveolar ridge atrophy poses a clinical challenge towards the fabrication of a successful prosthesis. Resorption of denture bearing areas results in an unstable non-retentive dentures associated with pain and discomfort. Prosthetic Rehabilitation of a patient with severely resorbed ridge is the most challenging therapy a prosthodontist can undertake. For a favourable prognosis of the denture therapy, impression technique selected should be based on the present state of the basal tissue support. This article presents rehabilitation of a patient with severely resorbed mandibular ridge with the application of neutral zone concept being incorporated into impression making in an effort to achieve successful complete denture therapy. Finally, patient had more stable, retentive and functionally efficient complete denture. In conclusion, neutral zone impression technique proved to be a quite effective method for prosthetic rehabilitation of patient with severe mandibular ridge resorption. DOI: http://dx.doi.org/10.3329/bjms.v13i4.15605 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.477-480